Genetic Diversity of the Family Francisellaceae, Analysis of the situation on tularemia Incidence in the Russian Federation in 2021, and Forecast for 2022 - T. Yu. Kudryavtseva (Проблемы особо опасных инфекций, 2022)
The review briefly outlines the current taxonomy of the most studied strains of the species belonging to the family Francisellaceae. Due to the significant genetic diversity within the family, the detection of Francisella tularensis, especially in environmental samples, becomes even more difficult and may lead to false positive results. A comparison of the incidence rates in European countries, in which the extensive epidemic manifestations of tularemia are recorded annually, namely Sweden, Finland, Norway and the Czech Republic, and in Russia over the past five years is provided. The paper presents the comparative dynamics of tularemia incidence in the territories of the Federal Districts of the Russian Federation in recent years. The dynamics of the incidence during epidemic outbreaks in the Republic of Karelia and the Omsk Region over the past few years is shown. 17 cases of human infection with the causative agent of tularemia were registered on the territory of the Russian Federation in 2021. Epizootic manifestations of the infection of varying degrees of intensity were detected in 45 constituent entities of the Federation. Against that background, sporadic cases of tularemia in humans were reported in 11 regions of the country. Six cultures of Francisella tularensis subsp. mediasiatica from different types of ticks were isolated in the Krasnoyarsk Territory, the Republic of Altai and the Altai Territory. Based on the analysis of the data presented, in 2022, epidemic complications in the form of sporadic cases of the disease are most likely to occur among the unvaccinated population in the territories of the Central Federal District – the Voronezh, Ryazan, Smolensk Regions and in Moscow; Northwestern Federal District – in the Arkhangelsk Region, the Republic of Karelia and in St. Petersburg; Volga Federal District – in the territories of Samara, Kirov Regions and Republic of Tatarstan; Ural Federal District – in the Khanty-Mansiysk and Yamalo-Nenets Autonomous Districts; Siberian Federal District – in certain districts of the Kemerovo, Novosibirsk, Omsk and Tomsk Regions, Altai and Krasnoyarsk Territories.